Вплив лазерного мікрорельєфного зміцнення на фізико-хімічні властивості фальцювальних планок зі сталі AISI 347 - Киричок, П. О.; Палюх, Д. О. (ТОВ «Видавництво Ліра-К», 2025)
The study investigates the process of laser-induced microrelief formation on the surface of folding plates made of AISI 347 stainless steel and AISI 1005 carbon steel. The research analyzes the physico-chemical changes in the surface layer after processing and their impact on mechanical properties, wear resistance, and corrosion resistance of the material. Optimal laser processing parameters for enhancing the performance characteristics of folding plates are identified.
Keywords: мікрорельєфне зміцнення; властивості фальцювальних планок